Determinants of Measles Immunization Completeness and the Effect of Community Health Education Among Parents in Banten Province, Indonesia - Ajeng Retno Setiawati; Daniel Huang; Vini Claudya Agustine Rajagukguk; Silviana Tirtasari (Community Medicine and Education Journal, 2026)
Measles remains a highly transmissible vaccine-preventable disease and a sensitive marker of immunization-system performance, with global elimination stalling as coverage falls below the 95% herd-immunity threshold; sub-optimal parental health literacy and incomplete immunization sustain community transmission in Indonesia. This study aimed to quantify parental knowledge, attitudes and practices (KAP) toward measles prevention, determine immunization completeness and its determinants, and evaluate a community health-education intervention. A cross-sectional community-diagnosis study with a single-group pre-/post-test design was conducted among 30 parents/guardians of children aged 0-59 months to primary-school age in a primary health center catchment area in Banten Province, Indonesia. Data were collected with a validated KAP questionnaire (Cronbach's alpha 0.76-0.83) and immunization-record screening; analyses included Wilson confidence intervals, McNemar tests, logistic regression and effect sizes. Baseline knowledge was low in 66.7% of respondents (95% CI 48.8-80.8), and measles-immunization completeness was 80.0% (95% CI 62.7-90.5), below the elimination target. Low parental knowledge showed the strongest, though non-significant, association with incomplete immunization (OR 3.00, 95% CI 0.30-29.94; adjusted OR 10.06, 95% CI 0.75-135.58, p=0.082). After health education, the proportion of respondents scoring >=70 rose from 10.0% to 93.3% (McNemar p<0.001; Cohen's h=1.98), and mean knowledge improved from 51.5 to 84.6 (Cohen's d_z=2.24). Community health education substantially improved measles-prevention literacy, while a residual immunization gap persisted. Strengthening parental education and immunization monitoring at the primary-care level supports measles control and advances SDG 3 and SDG 10.